ANALISIS PENERAPAN SISTEM DAN PROSEDUR PEMUNGUTAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) DI KOTA BLITAR - Hana, Ahmad Amril; Aji, Dhoni Saloka (Jurnal Ilmiah Cendekia Akuntansi, 2024)
This study aims to analyze the implementation of the system and procedures for the collection of Rural and Urban Land and Building Tax (PBB-P2) in Blitar City. The research employs a qualitative approach, utilizing data collection methods such as interviews, observations, and document studies. The findings indicate that although the PBB-P2 collection system has been implemented, several challenges remain, including a lack of public awareness, inaccurate data on tax objects, and a predominantly manual collection process. The study also highlights the importance of socialization and training for tax officials to enhance taxpayer compliance. Recommendations include the digitalization of the tax collection system and improved communication with the public. These findings are expected to contribute to the development of tax collection policies in Blitar City and other regions.